Factors Perceived by Caretakers as Barriers to Health Care for Under-Five Children in Mazabuka District, Zambia. (14th March 2013) - Halwindi, H.; Siziya, S.; Magnussen, P.; Olsen, A.
Abstract : In rural areas of Zambia primary health care is provided by rural health centres (RHCs). However, accessibility to these services is limited. In the catchment areas of two RHCs in Mazabuka district (Chivuna and Magoye RHCs) we investigated factors that caretakers perceived as barriers to health care for under five children and how they cope with the barriers. Ten Focus Group Discussions (FGDs) with caretakers of children under-five years of age and key informant interviews with six health workers from the two RHCs, and eight community health workers were conducted in May 2006. The major factors perceived as barriers were poor quality of health services, unavailability of medicines, financial constraints, weak outreach programmes, bad scheduling of health programmes, poor communication, long distance to RHCs and low awareness levels of the importance of taking children for child health week among caretakers. Caretakers' main coping strategy was the use of the folk sector of health care. The findings of this study highlight the challenges that exist in accessing of health care in resource-poor settings and underscore that the provision of health care services of good quality remains a major challenge.